(untitled) (TAMADDUN NURI JURNALI, 2025)
In scientific work, the toponyms of the singular were nasnifted and studied according to their lexico-spiritual nature. The study also focuses on the issue of the history of the area in which toponyms are studied, the occurrence of toponyms and their grammatical nature. The object and subject of scientific work consists of a set of toponyms, the methodological basis of which is the methods of scientific vision, analysis and research used in the study of proverbial horses in the field of onomastics.